Factors of chemoresistant pulmonary tuberculosis progression in patients receiving palliative treatment - O. M. Raznatovska; G. V. Khudiakov (Zaporožskij Medicinskij Žurnal)
Objective – to define factors of chemoresistant pulmonary tuberculosis (CRPTB) progression in patients receiving palliative treatment by means of their QL, TNF-α levels and body mass index complex assessment.